2020
DOI: 10.1093/restud/rdaa072
|View full text |Cite|
|
Sign up to set email alerts
|

Property Rights, Land Misallocation, and Agricultural Efficiency in China

Abstract: This paper examines the impact of a property rights reform in rural China that allowed farmers to lease out their land. We find the reform led to increases in land rental activity in rural households. Our results indicate that the formalization of leasing rights resulted in a redistribution of land toward more productive farmers. Consequently, output and aggregate productivity increased by 8 and 10%, respectively. We also find that the reform increased the responsiveness of land allocation across crops to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(69 citation statements)
references
References 47 publications
4
65
0
Order By: Relevance
“…China has changed the land structure of contracting production to households and liberalized land circulation, and land distribution has changed from absolute equality to relative equality. The land was redistributed to the peasants with higher productivity [9]. The land system has a profound effect on the income distribution of rural households [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…China has changed the land structure of contracting production to households and liberalized land circulation, and land distribution has changed from absolute equality to relative equality. The land was redistributed to the peasants with higher productivity [9]. The land system has a profound effect on the income distribution of rural households [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the Law of the People's Republic of China on Land Management (1998), which formally permits farmers to transfer their land-use rights, is intended to facilitate rural land transactions institutionally. As a result, about two-thirds of China's rural land-use rights have been redistributed, with more productive farmers receiving access to larger areas of land [26,27].…”
Section: The Household Contract Responsibilitymentioning
confidence: 99%
“…In 2003, China announced the Rural Land Contracting Law (RLCL), which provides legal protection for farmers to rent out or rent in the land. Chari et al (2017) found that the RLCL increased crop output and aggregate productivity by redistributing the land toward more productive farmers.…”
Section: Incomementioning
confidence: 99%